Black Garlic Supplementation and Glomerular Protection in Hyperuricemic Rats: A Study on Kidney Health Prevention - Wahyudin Wahyudin; Fajar Wahyu Pribadi; Gita Nawangtantrini; Muhammad Riski Fatah; Zainuddin Zainuddin (Journal of Public Health and Pharmacy)
Introduction: Hyperuricemia is a significant risk factor for the development of chronic kidney disease. Excessive uric acid can deposit in the kidneys, triggering inflammatory reactions and oxidative stress, leading to structural damage in the glomeruli. Black garlic, with its antioxidant and bioactive compounds, has the potential to protect the kidneys from hyperuricemia-induced damage. Our objective is to evaluate the effect of black garlic supplementation on the histopathological features of glomeruli in a hyperuricemic rat model.